Domestic Violence in Pregnant Women: A Study Conducted in the Postpartum Period of Adolescents and Adults. Issue 6 (March 2019) - Lima, Lucia Helena Mello de; Mattar, Rosiane; Abrahão, Anelise Riedel
The aim of this study was to estimate the prevalence of domestic violence in adolescent and adult mothers who were admitted to obstetrics services centers in Brazil and to identify risk factors of domestic violence and any adverse obstetric and perinatal outcomes. Researchers used standardized interviews, the questionnaire Abuse Assessment Screen, and a review of patients' medical records. Descriptive statistical analyses were also used. The prevalence of domestic violence among all participants totaled 40.1% (38.5% of adolescents, 41.7% of adults). Factors associated with domestic violence during pregnancy were as follows: a history of family violence, a greater number of sexual partners, and being a smoker. No statistically significant association was found for adverse obstetric and perinatal outcomes. Results showed that, in Vitória, Espírito Santo, Brazil, pregnancy did not protect a woman from suffering domestic violence.